Nowelizacja ustawy Prawo o stowarzyszeniach i jej wpływ na funkcjonowanie trzeciego sektora ‒ zagadnienia wybrane - Mielczarek, Justyna; Mikołajów, Konrad (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Associations are the largest group of non-governmental organizations, forming so-called “Third sector”. This topic is important because of the amendments to the Law on Associations, which introduced major changes to the functioning of these organizations, which primarily concerns the reduction of the minimum number of association members that would allow the establishment of associations or changes in the supervision of their activities.
Keywords: amendment; associations; third sector; non-governmental organizations